THE EFFECT OF READING ANXIETY ON THE READING PERFORMANCE OF NON-ENGLISH DEPARTMENT EFL STUDENTS - Steffie Mega Mahardhika; Kristin Marwinda (Humaniora Scientia, 2025)
The importance of mastering English in the workplace urgently necessitates higher education not only from English language programs but also from other programs of English to prepare language skills. The researcher's concern about the lack of students' ability to master English, especially reading skills, is noteworthy. This is a significant concern because students appear anxious and fearful when asked to demonstrate their reading skills, thereby impacting their performance. Poor reading performance not only results in pronunciation errors but also in issues such as improper intonation and disregard for punctuation. Furthermore, the most critical aspect is that both the reader and the listener fail to understand the text being read, thus defeating the primary purpose of practicing English text reading. This research investigates whether poor reading performance is due to the anxiety they experience. This study using a qualitative method involving students from outside the English language program, specifically students from the Faculty of Economics and Business, 17 August 1945 University, Semarang. They were given a questionnaire to answer related to this research. The questionnaire is analyzed and supported by previous research. The results of this research indicate that students experience anxiety when asked to read using English as a foreign language, which affects their reading performance.